Apparent latent structure within the UK Biobank sample has implications for epidemiological analysis - Simon Haworth (Nature Portfolio, 2019)
Population structure can bias the results of genetic and epidemiological analysis. Here, Haworth et al. report that fine-scale structure is detectable in apparently homogeneous samples such as ALSPAC when measured very precisely, and remains detectable in UK Biobank despite conventional approaches to account for it.